A proteomic investigation of isogenic radiation resistant prostate cancer cell lines. Issue 5 (30th June 2021) - Kurganovs, Natalie; Wang, Hanzhi; Huang, Xiaoyong; Ignatchenko, Vladimir; Macklin, Andrew; Khan, Shahbaz; Downes, Michelle R.; Boutros, Paul C.; Liu, Stanley K.; Kislinger, Thomas
Abstract: To model the problem of radiation resistance in prostate cancer, cell lines mimicking a clinical course of conventionally fractionated or hypofractionated radiotherapy have been generated. Proteomic analysis of radiation resistant and radiosensitive DU145 prostate cancer cells detected 4410 proteins. Over 400 proteins were differentially expressed across both radiation resistant cell lines and pathway analysis revealed enrichment in epithelial to mesenchymal transition, glycolysis and hypoxia. From the radiation resistant protein candidates, the cell surface protein CD44 was identified in the glycolysis and epithelial to mesenchymal transition pathways and may serve as a potential therapeutic target.